1994
DOI: 10.1111/j.1472-765x.1994.tb00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction identification of Salmonella serotypes

Abstract: Seventy-seven Salmonella isolates comprising 61 different serotypes were subjected to polymerase chain reaction (PCR) fingerprinting using two primersets. Primerset L1/G1, amplifying the spacer regions between the 16S and 23S rRNA genes, resulted in simple PCR fingerprints. However, in some cases PCR amplification of different Salmonella serotypes with primerset L1/G1 resulted in identical fingerprint profiles. Fingerprints obtained with the ERIC primerset, that matches the enterobacterial repetitive intergeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 13 publications
4
0
0
Order By: Relevance
“…Our result is consistent with findings of Van Lith [37], who found each serotype was characterized by a unique DNA profile however Burr et al characterized Salmonella serotypes and found that every isolate had a unique fingerprinting but the serotypes were not grouped together in major branches, thus, serotypes were not identified by ERIC-PCR [38]. …”
Section: Discussionsupporting
confidence: 91%
“…Our result is consistent with findings of Van Lith [37], who found each serotype was characterized by a unique DNA profile however Burr et al characterized Salmonella serotypes and found that every isolate had a unique fingerprinting but the serotypes were not grouped together in major branches, thus, serotypes were not identified by ERIC-PCR [38]. …”
Section: Discussionsupporting
confidence: 91%
“…In this study, the usefulness of ERIC-PCR in genetic discrimination of S. Agona and S. Weltevreden has been revealed, in agreement with those of other researchers (Van Lith and Aarts 1994;Millemann et al 1996;Swanenburg et al 1998;Lim et al 2005).…”
Section: Eric-pcrsupporting
confidence: 93%
“…They reported that the techniques were able to discriminate among Salmonella isolates with similar serotypes. According to other reports, the ERIC1R–ERIC2 primer set (the primers employed in this study) had high discriminatory power on Salmonella isolates (Lith and Aarts ; Albufera et al . ).…”
Section: Discussionsupporting
confidence: 59%
“…They reported that the techniques were able to discriminate among Salmonella isolates with similar serotypes. According to other reports, the ERIC1R-ERIC2 primer set (the primers employed in this study) had high discriminatory power on Salmonella isolates (Lith and Aarts 1994;Albufera et al 2009). In contrast to this, Milleman who tested 85 Salmonella Typhimurium isolates from a group of 10 cows at different stages reported that ERIC-PCR could not be used to discriminate Salmonella isolates when the same primer sets were used (Millemann et al 2000).…”
Section: Discussionsupporting
confidence: 57%